The Relationship between the Intensity of Group Guidance Services and Students' Career Readiness - Hamdani -; Selfi; Resqi Amelia; Ana Fitriani (Institut Agama Islam Negeri Parepare, 2026)
This study is motivated by the low level of career readiness among university students, as reflected in their limited understanding of the world of work and confusion in making career choices. This study aims to examine the effect of the intensity of group counseling services on students' career readiness. This research employed a quantitative, correlational design. The sample consisted of 33 students selected through purposive sampling. The research instrument was a Likert-scale questionnaire. The data were analyzed using the Pearson correlation test in Jamovi. The results indicate a very strong and significant relationship between the intensity of group counseling services and students' career readiness, with a correlation coefficient of 0.992 and a p-value of < 0.001. This finding suggests that higher participation intensity in group counseling services is associated with higher levels of career readiness among students.